1979
DOI: 10.1111/j.1398-9995.1979.tb02001.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Treatment with Beclomethasone Dipropionate Aerosol in Asthmatic Children, with Special Reference to Growth

Abstract: Thirty-one children, 19 boys and 12 girls, aged 3.4--10.8 years, with severe perennial bronchial asthma were treated with beclomethasone dipropionate aerosol (BDA) for 16-40 months. The dose was initially 400 micrograms a day and was gradually reduced to the lowest level giving control of symptoms. Earlier steroid or ACTH-treatment in six children was stopped during the BDA-treatment. At the start of the treatment the mean deviation of height compared with normal values for Swedish children was -0.10 s.d. for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The direct influence of asthma on growth makes it difficult to assess the effects of corticosteroids in crosssectional studies, although the majority of these studies have shown no effect of inhaled corticosteroids [67][68][69][70][71][72][73][74][75][76]. Longitudinal studies have also generally failed to demonstrate any significant effect of inhaled corticosteroids on statural growth in doses up to 800 µg·day -1 for up to 5 yrs of treatment [62,[77][78][79].…”
Section: Effect Of Corticosteroids On Growthmentioning
confidence: 99%
“…The direct influence of asthma on growth makes it difficult to assess the effects of corticosteroids in crosssectional studies, although the majority of these studies have shown no effect of inhaled corticosteroids [67][68][69][70][71][72][73][74][75][76]. Longitudinal studies have also generally failed to demonstrate any significant effect of inhaled corticosteroids on statural growth in doses up to 800 µg·day -1 for up to 5 yrs of treatment [62,[77][78][79].…”
Section: Effect Of Corticosteroids On Growthmentioning
confidence: 99%
“…'0 11 The effect of ICT on linear growth, is however, controversial. 3 [12][13][14] This study evaluated the effects of ICT and the severity of asthma on linear growth in prepubertal children with severe chronic bronchial asthma, many of whom were poorly controlled despite higher than conventionally recommended doses of ICT.…”
mentioning
confidence: 99%
“…Compared with oral corticosteroids, inhaled corticosteroids caused dramatically fewer side effects, specifically appearing not to impair growth [14,15] and possibly resulting in improved growth [16]. However, these studies reported on small numbers of children and were designed to evaluate therapeutic efficacy.…”
Section: Historical Backgroundmentioning
confidence: 97%